analisis implementasi gaya hidup berkelanjutan di kalangan mahasiswa - WINDIANTI Windi; Feri Maulana; Hamsirah Hamsirah (Journal of Economic and Business Analysis, 2024)
This study examines the implentation of sustainble lifestyles among university students in Indonesia, focusing on the challenfes faced in achieving the Sustainable Development Goals (SDGs). The findings reveal that despite Indonesia’s SDG index ranking dropping from 75th in 2023 to 78th 2024, students awareness of environmental issues has shown positive trajectory. A quantitative research method was employed, utilizing primary data conducted through questionnaires distributed to respondents, the study measured key indcators encompassing care, proactivity, productivity, and resource management intellingence. The results indicate that students with high levels environmental awareness are more likely to actively adopt environmentally frendly practices. The article highlights the importance of integrating environmental education into academic curricula and emphasizes the need for government support in providing infrastructure that facilitates sustainable living. By doing so, it is expeceted that university students will play an active role in fostering a more sustainable amd improved environment.